Moral approaches and roles of Prophet Muhammad (S.A.W) in empowering persons with special need - Islam, Md. Sirajul; Samsudin, Sofiah (AENSI Publications, Jordan, 2018)
The pre-Islamic society used to exclusion persons with special needs. The last Messenger of Allah (S.A.W) established their rights. The main aim of this study is finding His methodology in empowering this form of people. In order to achieve this objective first of all we have collected data from seven authentic sources of the Prophetic traditions; Sahih al-Bukhari, Sahih Muslim, Sunan abi Daud, Sunan ibn Mazah, Sunan Al-Tirmiji, Masnad Ahmad ibn Hambal and Sua’bul Eman. The study has found five moral approaches and twelve moral roles by analyzing collected data from the Prophetic traditions in empowering persons with special needs. These approaches and roles in dealing with them played as being the key to overcome the plight of special needs. Subsequently, these approaches and roles led to blueprint on a unique development of their life. In fact, empowering this group of people is a major challenge in the contemporary world. In view of such conditions, this study will generate a great deal of interest in this issue.